Gênero e política externa: uma análise do governo Bolsonaro - Paris, Carolina Fernandes (2024)
This dissertation proposes an analysis of how gender policies were handled by the Bolsonaro Administration concerning Brazilian Foreign Policy. After presenting this ideology’s main characteristics and how it resonates with the Far Right movement worldwide, a way of action using Process Tracing is then formulated to establish causal inferences among Brazil’s international insertion and its domestic correlation in hope of mapping its trajectory in gender. To outline this government's actions, characterized by an affront to the current international order and an ultra-conservative religious profile, the study analyzes speeches from key Bolsonaro thinkers that incorporated anti-gender rhetoric, delivered at venues where Brazil had previously been a pioneer in gender issues. The findings indicate undeniable damage to Brazil's international image due to the dismantling of the gender agenda during Bolsonaro's administration, though the internal impact was less severe